Development of a Primary Human Co-Culture Model of Inflamed Airway Mucosa - Lael M. Yonker (Nature Portfolio, 2017)
Abstract Neutrophil breach of the mucosal surface is a common pathological consequence of infection. We present an advanced co-culture model to explore neutrophil transepithelial migration utilizing airway mucosal barriers differentiated from primary human airway basal cells and examined by advanced imaging. Human airway basal cells were differentiated and cultured at air-liquid interface (ALI) on the underside of 3 µm pore-sized transwells, compatible with the study of transmigrating neutrophils. Inverted ALIs exhibit beating cilia and mucus production, consistent with conventional ALIs, as visualized by micro-optical coherence tomography (µOCT). µOCT is a recently developed imaging modality with the capacity for real time two- and three-dimensional analysis of cellular events in marked detail, including neutrophil transmigratory dynamics. Further, the newly devised and imaged primary co-culture model recapitulates key molecular mechanisms that underlie bacteria-induced neutrophil transepithelial migration previously characterized using cell line-based models. Neutrophils respond to imposed chemotactic gradients, and migrate in response to Pseudomonas aeruginosa infection of primary ALI barriers through a hepoxilin A3-directed mechanism. This primary cell-based co-culture system combined with µOCT imaging offers significant opportunity to probe, in great detail, micro-anatomical and mechanistic features of bacteria-induced neutrophil transepithelial migration and other important immunological and physiological processes at the mucosal surface.